Maintenance of a Ground Anchor Based on Monitoring of Residual Tensile Loads - Sakai, Toshinori (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Anchors have been used for many years as restraint structures to maintain the stability of slopes. As the restraining effect of such slopes is exerted by the tensile force acting on the involved anchors, investigation of this tensile force is important when maintaining anchors. As multiple anchors are installed on slopes, investigation of numerous anchors is essential to determine the tensile force. This study describes the maintenance of anchors based on the residual-load results obtained using the involved SAAM (Sustainable Asset Anchor Maintenance) system, which uses a compact and lightweight SAAM jack capable of performing lift-off tests on numerous anchors.